Prednostne delnice brez glasovalne pravice in vinkulirane delnice pri sklepanju o rednem povečanju osnovnega kapitala - Drnovšek, Gregor (Podjetje in delo, 2014)
Due to the protection of shareholders the Slovenian Companies Act (ZGD-1) states the exclusive right of the General meeting of Shareholders to decide on regular increase of subscribed capital. While it goes without saying that such change is decided by the holders of the ordinary shares, the Law in some cases demands that in making such decision holders of the preferred nonvoting shares should participate as well. If the subscribed capital is to be increased with the issue of shares with restricted transferability, then in some cases the shareholders have to specially agree on that. Described cases are the subject of this article.
Keywords: Das Kapital; delnice; delniške družbe; kapital; management; odločanje; upravljanje